173k views
3 votes
Use f(x) = 2 x and f-'(x) = 2x to solve the problems.

f2) = 0


f(1) =


f'(2)) =


DONE

1 Answer

5 votes

Answer:


f(2) = 1


f(1) = (1)/(2)


f^(-1)(2)=4

Explanation:

Consider the provided functions.


f(x) = (1)/(2)x


f^(-1)(x)=2x

Find f(2) as shown.

Substitute x=2 in
f(x) = (1)/(2)x


f(2) = (1)/(2)*2


f(2) = 1

Find f(1) as shown.

Substitute x=1 in
f(x) = (1)/(2)x


f(1) = (1)/(2)

Find f'(2) as shown.

Substitute x=2 in
f^(-1)(x)=2x


f^(-1)(2)=2(2)


f^(-1)(2)=4

User Barbiepylon
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.